MEDIA PEMBELAJARAN BERBASIS IT SEBAGAI INOVASI PEMBELAJARAN PADA JENJANG TAMAN KANAK-KANAK (STUDI KASUS GURU TAMAN KANAK-KANAK MUSLIMAT NU MASLAKUL HUDA) - M. Ghofar Rohman; Purnomo Hadi Susilo (Universitas Islam Lamongan, 2018)
The purpose of this research was to determine the improvement of the ability of kindergarten teachers in the preparation of learning media, and to improve the ability of teachers to innovate in developing information technology(IT)-based learning media. The problem in education in kindergarten lies in the ability of teachers in teaching and learning activities in which teachers teach without developing their abilities in developing learning media used, the lack of teachers' ability to use computers, and lack of willingness to improve creativity in providing learning media.This research uses a classroom action research (CAR) model with a collaborative model between the cycle models developed by Kemmis and Taggar. The results of this study indicate that there is an increase starting from the initial research activities there is a percentage of the ability of teachers in developing learning media is equal to 49.62%, the percentage of teacher completeness is 23.08%.Finally, in the second cycle there was an increase in the percentage of the teacher's ability to develop learning media at 91.54%, the percentage of teacher's completeness was 100%. the improvement of teacher information technology competencies can stimulate teachers to innovate in developing learning media. Kata kunci: Learning Media, Kindergarten Teachers, Information Technology.